Upaya Kepala Sekolah Untuk Peningkatan Kompetensi Profesional Guru - Mohamad Muspawi; Bradley Setiyadi; Gunawan Gunawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The purpose and target of this study was to describe the efforts of the principal to improve the professional competence of teachers in Public Elementary School No. 162/I Bukit Sari Village, Maro Sebo District. The aspects studied included the efforts of the principal to improve teacher professional competence, as well as inhibiting factors. The author uses a qualitative approach and chooses the type of case study. The principal is a subject. The principal and teacher are the data sources used as sources of information. Data collection uses interview techniques and documentation studies. Analyzing data is done by reviewing, data reduction, presenting data, and verifying data to then draw conclusions. The technique of checking the validity of the data using source triangulation. The results of this study explain that the efforts of principals to improve teacher professional competencies are by implementing a coaching process and involving teachers in various educational activities and training, seminars, workshops, and Teacher Working Groups. The obstacles are: 1) Teachers and schools have difficulty accessing information because the internet connection or network is very slow. 2) There are still some teachers who do not understand the concept of interrelationship between subjects. Based on the results of the study it is recommended that: 1) The principal must be more active in developing all teaching staff. 2) Immediately resolve the problem of internet network connection and fulfill other supporting facilities. 3) Teachers must be able to use various learning methods.